The interplay of lexical and grammatical development in Greek-Albanian bilingual children: evidence from the majority and the heritage language - Kaltsa, Maria; Prentza, Alexandra; Prela, Leonarda; Tsimpli, Ianthi Maria (International Journal of Bilingual Education and Bilingualism, 2024)
The present paper aims to investigate the interplay of lexical and grammatical development in school-aged Greek-Albanian bilingual children by providing evidence both from majority, Greek, and heritage, Albanian. To this end, 47 8 to 10-year-old bilingual children were tested by means of expressive vocabulary tests in Greek and in Albanian, while their grammatical skills were evaluated by means of the LITMUS Sentence Repetition Task administered in both languages. Additionally, input-related measures in both languages, such as oral language practices, literacy, and educational practices were used to assess the bilingual experience and examine how it would correlate with lexical and grammatical skills. The analysis showed that within each language, lexical and grammatical skills were closely related both for the majority and the heritage language, while when examining across-language effects, grammatical skills in the heritage language were correlated with grammatical skills in the majority language. Concerning the role of input, we found that input in the heritage language supported skills both in the heritage and the majority language. The study's contribution is that by providing novel evidence from this specific language pair it shows that supporting the use of heritage language can boost language skills in both languages.
CRIS-Team Scopus Importer:2024-11-01
Keywords: Albanian; child bilingualism; grammatical development; Greek; heritage language; lexicon; majority language